Bagan Kendali Variansi dengan Penambahan Variabel pada Nilai Ekspor dan Berat Ekspor - Widyanti Rahayu; Daisy Salsabilah Kusuma (Jurnal Statistika dan Aplikasinya, 2023)
To create products or services that meet certain quality standards, supervision and control need to be carried out. Quality control monitors changes in the level of variability, or the level of average, or both to observe changes that occur during the production process. The monitoring stage begins with controlling variability, followed by controlling the average level. Walter A. Shewhart (1920) introduced several variability control charts, including the S2 variance control chart, which involves one quality characteristic, Y. Riaz (2008) introduced a regression-type estimator of the variance of Y using additional correlated information X. This control chart is known as the Vr control chart and shows better results than the S2 control chart. Furthermore, Riaz (2009) introduced a Vt control chart, created based on a ratio-type estimator of the variance of Y. The accuracy of the Vt control chart increases as the value increases. The S2, Vr, Vt control chart is used to monitor the variability of export value (Y) using additional information on export weight (X). All three charts indicate that the variability in export values is out of control. Comparison of the results obtained from the Vt, Vr, and S2 control charts is made by examining the power curve of each chart. Specifically, it was observed that the Vt control chart produces more consistent and accurate conclusions.